Exploring the nature of buyer-seller relationships in the Western Australian wine industry - Batt, Peter; Wilson, H. (Griffith University, 2000)
Since the majority of grape growers and wine makers in Western Australia are family enterprises, they are highly risk averse and suspicious of unfamiliar exchange partners. In the absence of formal contracts, the nature of the relationship between wineries and grape growers is largely one of interdependence. To produce good quality wines, wineries need a reliable supply of good quality grapes, which, in turn, requires technical information to be exchanged and production activities to be coordinated. Since both parties are mututally dependent, uncertainty is reducted and there is a high degree of satisfaction, trust and commitment to the relationship.